Sustainable Cultural Tourism in the Age of (Green) AI: Opportunities and Challenges for Heritage Sites - Fajar Santoso; bhenu artha; Sadath M. Nur; Felyanah Dessy Cinthya Putri; Adista Ika Julia (Fakultas Ekonomi, Universitas Ekasakti, 2026)
Cultural heritage artifacts can be protected and repaired to serve as the foundation for sustainable tourism and related enterprises. Intangible cultural heritage, in particular, stands out as a kind of cultural authenticity, therefore it can be used to generate socioeconomic benefits in the cultural tourism industry. Virtual Reality (VR) and Augmented Reality (AR) are now nearly universally used, resulting in considerable changes in manufacturing and consumption processes. These technologies have found widespread use in marketing, promotion, and even product development. This theoretical overview brings together recent research on how artificial intelligence (AI) is altering sustainable cultural and heritage tourism. It maps key theoretical lenses (socio-technical systems, sustainability/SDG frameworks, cultural heritage theory, experience economy, and technological determinism), identifies major AI-enabled opportunities (interpretation, accessibility, demand management, conservation, community empowerment), and highlights critical challenges (authenticity, equity, data governance, commodification, environmental footprint, skills). AI, AR, VR, and robotics form a tightly coupled technology ecosystem whose combined effect on heritage tourism is simultaneously enabling and disruptive. Thoughtful stewardship, community co-ownership, and interdisciplinary evaluation are essential to harness benefits, enhanced interpretation, conservation efficiency, accessibility while guarding against threats to authenticity, equity, and sustainability. The study concludes with policy and research recommendations for heritage managers, policymakers, and researchers seeking to strike a balance between technological innovation, sustainability, and cultural integrity.